2021
DOI: 10.1099/ijsem.0.004597
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas cremoris sp. nov., a novel proteolytic species isolated from cream

Abstract: During a study investigating the microbiota of raw milk and its semi-finished products, strains WS 5106T and WS 5096 were isolated from cream and skimmed milk concentrate. They could be assigned to the genus Pseudomonas by their 16S rRNA sequences, but not to any validly named species. In this work, a polyphasic approach was used to characterize the novel strains and to investigate their taxonomic status. Examinations based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…cremoris sp. nov. was reported in the previous study ( Hofmann et al, 2021 ). For example, ANIm comparisons indicated that the type strain WS 5106 was a novel species within the P .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…cremoris sp. nov. was reported in the previous study ( Hofmann et al, 2021 ). For example, ANIm comparisons indicated that the type strain WS 5106 was a novel species within the P .…”
Section: Discussionsupporting
confidence: 83%
“…A similar case about the taxonomic characterization of P. cremoris sp. nov. was reported in the previous study (Hofmann et al, 2021). For example, ANIm comparisons indicated that the type strain WS 5106 was a novel species within the P. fluorescens subgroup, but the pairwise ANIm values of 90.1 and 89.8% showed that WS 5106 was most closely related to Pseudomonas nabeulensis CECT 9765 T and Pseudomonas kairouanensis CECT 9766 T (Hofmann et al, 2021).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Due to the permanent cooling of the milk during the whole processing line, the microbiota of raw milk shifts mainly to psychrophilic organisms, especially Pseudomonas species [6]. In milk and dairy products, several novel Pseudomonas species have been identified, mainly from the Pseudomonas fluorescens lineage ( fluorescens and fragi subgroup) [7–11]. Several studies have shown that the psychrophilic genus Pseudomonas is one of the most prevalent and abundant genera in raw milk [6, 12].…”
Section: Full-textmentioning
confidence: 99%